THE USE OF GOOGLE CLASSROOM IN EFFECTIVENESS IN ELT: SYSTEMATIC REVIEW - Qibtiya, Maryatul; Amaliyah, Neli; Anindya, Fidela; Fatimah, Dinda; Tarihoran, Naf'an (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
The integration of technology in education has revolutionized teaching and learning practices across various disciplines. This comprehensive review seeks to investigate the effectiveness of Google Classroom in Teaching English (ELT) by examining the existing literature, to address the need for a comprehensive understanding of its impact on language learning. In addition, this review contributes to a cumulative understanding of technology integration in language education, thus informing future research directions and pedagogical approaches. This study uses the method of systematic review for the method to apply in this paper. The purpose of this study is to investigate the role of Google classroom in ELT by analyzing the literature. The results of this systematic review show that the platform is highly effective from two important aspects, namely, from the perspective of ELT and writing instruction. Teachers and educational institutions should integrate Google Classroom as one of the supporting tools in the learning process and the development of creative and effective communication and writing skills. This research also provides a new view in developing more innovative learning strategies and adjusting to the digital era that is currently developing.